Relationship between Ratio of the Head Circumference to the Width of the Anterior Maxillary Teeth - M Bonakdarchian; M Nekuei Parvar; N Lotfi Zadeh (Isfahan University of Medical Sciences, 2007)
Introduction: The selection of the 6 anterior maxillary teeth in complete denture constitutes the first esthetic foundation for edentulous patients. Many attempts have been made to establish methods of estimating the combined width of anterior maxillary teeth.The aim of this investigation was to determine whether a relationship exists between the widths of the upper anterior teeth to head circumference.Methods and Materials: This Resciptiue-Analytic survey was done on 98 dentistry students (including 49 women and 49 men 18-40 years old range). Using the digital caliper and flexible ruler, the combined width of the 6 anterior maxillary teeth at their widest dimension on crown region, were measured extra orally (on their casts). The circumferences of head were measured by meter which was crossed from Glabella and occiput. Data analysis was done by Pearson correlation coefficients and T-student tests.Results: In men, the mean of the ratio between the head circumferences to the combined widths of the anterior maxillary teeth, which were measured by flexible ruler, was 10.6:1. Using digital caliper for measurement, the mean of the ratio was 12.32:1.In women, the mean of the ratio between the head circumferences to the widths of the anterior maxillary teeth, which were measured by flexible ruler, was 10.4:1. Using digital caliper for measurement, the mean of the ratio was 12.15:1.The Pearson correlation coefficient between head circumferences and combined width of anterior maxillary teeth was 0.343 and 0.508 using flexible ruler and digital caliper respectively.Conclusion: Within the limitations of this study, the results suggest that head circumference can be used as a preliminary method for determining the width of the anterior maxillary teeth for edentulous patients; especially, when using digital caliper for the measurement of the widths of the anterior maxillary teeth. But no significant relationship exists between upper ratio and sex.Key words: Head Circumference, Anterior Maxillary Teeth, Dental Width.